Adenomatoid Odontogenic Tumor of the Mandible: An Unusual Clinical Presentation - Rai, Amita; Dali, Mamta; Koirala, Bandana; Shrestha, Sneha; Acharya, Pradeep; Shrestha, Ashish (Birat Journal of Health Sciences, 2018)
Adenomatoid odontogenic tumor (AOT) is a rare benign neoplasm of odontogenic epithelial origin. A 12-year-old male reported to the department of pedodontics and preventive dentistry with swelling on lower part of face since seven months. On examination, firm to hard, nontender swelling, sized approximately 3 × 3 cm, extending from mandibular left canine to right lateral incisor with expansion of labial and lingual cortices was present. Radiograph revealed a well demarcated unilocular radiolucency exhibiting sclerotic border with flecks of calcification and displaced roots of mandibular anteriors and expansion of both cortices. Incisional biopsy confirmed the diagnosis of AOT. Enucleation of the lesion along with #31, 32 and curetiage was done under general anesthesia. Ribbond fiber prosthesis was given to maintain the arch integrity and esthetics. AOT in mandible (35%) of young male (36%) of extrafollicular variant (24%) is rare. We may encounter only 2-3 out of 100 AOT cases as typical as the case presented here. BJHS 2018;3(2)6: 504-507.